360 Derece Performans Değerlendirme Sürecinin Öğretim ElemanlarıÜzerindeki Etkisi: Bir Vakıf Üniversitesi Yabancı Diller YüksekokuluÖrneği - (:unkn) unknown (My University, 2017)
Bu araştırmanın amacı, bir vakıf üniversitesinin yabancı diller yüksekokulunda uygulanan 360 derece performans değerlendirme sürecinin öğretim elemanları üzerindeki etkisini incelemektir. Araştırma, nitel araştırma yöntemlerinden fenomenoloji deseniyle yürütülmüştür. Araştırma kapsamında İstanbul ilindeki bir vakıf üniversitesi yabancı diller yüksekokulunda okutman kadrosunda bulunan öğretim elemanlarıyla odak grup görüşmeleri yapılmıştır. Çalışma grubu, gönüllülük esaslı amaçlı örnekleme yöntemiyle oluşturulmuştur. Elde edilen veriler kodlanarak kategoriler altında toplanmış ve betimsel analize tabi tutulmuştur. Araştırma bulgularına dayanarak 360 derece performans değerlendirme sürecinin bu kurumda çalışan öğretim elemanları üzerinde negatif etkileri olduğu söylenebilir. Bununla birlikte katılımcılara göre bu değerlendirme süreci adil ve şeffaf olmayan bir şekilde işlemekte olup, bu durum öğretim elemanlarının iş motivasyonlarını olumsuz yönde etkilemektedir.

The purpose of the study is to examine the effect of 360 degree performance evaluation process in practice on instructors working at a foreign languages preparatory school of a foundation university in Turkey. Phenomenology model, one of the qualitative methods, was used in the research. The study's data obtained by using interview method which is one of the quality research techniques. In this research, a focus group meeting was held with foreign language instructors at a foundation university in Istanbul, Turkey. The working group was created having a specified goal sampling method. The obtained data were gathered under categories by coding and descriptive analysis was made. Based on the findings of the study, it can be said that the 360 degree performance evaluation process has negative effects on the instructors. According to participants the evaluation process is not only unfair and non transparent, but also this situation negatively affects their job motivations.
The Effect of 360 Degree Performance Evaluation Process on Instructors: The Case of the Foreign Languages Preparatory School of a Foundation University in Turkey
Keywords: Eğitim, Eğitim Araştırmaları